Structure and expression of the long noncoding RNA gene MIR503 in humans and non-human primates. (15th June 2020) - Choudhari, Ramesh; Yang, Barbara; Rotwein, Peter; Gadad, Shrikanth S.
Abstract: Recent technical and other advances in genomics provide unique opportunities to improve our understanding of human physiology and disease predisposition through a detailed analysis of gene structure and expression by examining data in public genome and gene-expression repositories. Yet, the vast majority of human genes remain understudied. This is particularly true of genes for long noncoding RNAs (lncRNAs). Here, we describe the detailed characterization of MIR503HG, a lncRNA gene found on the X chromosome in humans. Using information extracted from public databases, we show that human MIR503HG is a 5-exon gene, and that it is highly conserved among 5 non-human primates spanning over 85 million years ago of evolutionary diversification. MIR503HG is transcribed and processed into multiple distinct RNAs in each of these species through differential exon use and alternative RNA splicing, with a higher abundance of transcripts being found in reproductive tissues, especially during the early stages of ovary and testis development, indicating a possible role in reproductive biology. Furthermore, in select reproductive system cancers, MIR503HG transcripts are downregulated, with higher levels of RNA expression being associated with clinical outcomes. Collectively, these investigations show how the use of genomic, gene expression, and other genetic resources can lead to new insights about human biology and disease, and argue that MIR503HG is worthy of additional study. Highlights: Long intergenic noncoding RNA MIR503HG is highly conserved in non-human primates. MIR503HG transcribed into RNAs through differential exon use and alternative RNA splicing. MIR503HG transcripts are downregulated in select gynecological cancers.